Clients’ perception towards the functions and effectiveness of the reconciliation process at the marriage tribunal - Abdul Hak, Nora; Rahmat, Nur Ezan; Md Hashim, Noraini (2015)
The conciliatory bodies appointed under section 106 of the Law Reform (Marriage and Divorce) 1976 Act are not effective while, the existing legal provisions concerning reconciliation and conciliation processes are not adequate to reconcile the matrimonial disputes of non-Muslims in Malaysia. The focus of discussion is only on Marriage Tribunal. This paper discusses and explains the analysis and finding of data from the questionnaire distributed to the respondents. In this study, the questionnaires were distributed among the respondents in a few selected places. Detailed evaluation of the data used in achieving its objectives and to answer the research questions of the study is discussed. This paper begins with the interpretation on descriptive statistics of demographic characteristics of the respondents, followed by test of the knowledge of the respondents on the laws and their rights, satisfaction of the respondents with the process of reconciliation and its officers, and lastly, on the outcome of the process itself. Subsequent to the descriptive statistic, every part of the questionnaires was tested by using the normality test to determine if a data set is well-modelled by a normal distribution. The statistical methods employed in this study range from frequency distribution, descriptive statistics, and non-parametric analysis. With descriptive data, transforming the raw data into tables and charts is part of the process of making sense of the data, so that the meaning and significance of the data can be comprehended. Finally, the finding shows that although the respondents are quite satisfied with the reconciliation sessions and the officers, but they still fail to reconcile the disputing parties. Suggestions are given to improve the existing practice of reconciliation.